The New Economics of Banking - David T. Llewellyn (SUERF - The European Money and Finance Forum, 1999)
All aspects of banking business are being radically transformed and to an extent that is changing the fundamental economics of the banking firm and the banking industry. This is because of three dominant factors: a series of powerful pressures acting simultaneously; technology is changing the very core of banking business: infor-mation advantages, processing, moni-toring, delivery, etc; and because, as a result of these pressures, competition is increasingly developing from outside the traditional banking industry. The paper reviews the pressures impinging on the economics of banking and considers their implications for the structure of the banking industry; the business operations of banks, and the structure of the banking firm."
Keywords: 330; Economics of banking; Bank; Theorie